The Strategy of Ikatan Motor Indonesia (IMI) in Building Organizational Branding through the Indonesia International Motor Show (IIMS) 2025 - Wibowo, Mazaya Fathia Adreya; Auliya, Anisatul (Journal of Indonesian Tourism and Policy Studies, 2025)
Automotive industry is one of growing competitive industry, organisational branding is essential to shape public image and loyalty. This research aims to analyse the branding strategy of the Ikatan Motor Indonesia (IMI) through its participation in the Indonesia International Motor Show (IIMS) 2025. The research used a qualitative method with a case study approach. Data collection techniques were conducted through in-depth interviews, direct observation, literature study, and documentation. Data analysis used the Miles and Huberman model through collection, reduction, data presentation, and conclusion drawing and verification. The results showed that IMI successfully utilised the five main elements of branding according to Dinnie, (2022), namely identity, image, positioning, personality, and brand communication through programmes such as IMI Goes to Campus, partner collaborations, talk shows, and podcasts. This strategy is effective in shaping IMI's image as an organisation that is inclusive, educative, and relevant to the younger generation. Future research is recommended to evaluate the long-term impact of this branding strategy on automotive community loyalty.